Breaking barriers: Indigenous nurse navigator role in oncology care for the Inuit - Carolyn Roberts (Pappin Communications, 2024)
Individuals who live in the north of Canada face many challenges when they are diagnosed with cancer. Accessing cancer care usually means having to travel to a cancer centre in southern facilities and stay in a city away from family, local community, language and culture. The Indigenous Cancer Program atThe Ottawa Hospital was established to assist these individuals in navigating a complex and unfamiliar system of care. The First Nations, Inuit, Métis Nurse Navigator role was designed to collaborate with these patients and develop interventions to meet their unique needs. Recently, a satellite oncology clinic was opened in the territory of Baffin Island Nunavut where patients can be assessed, receive cancer immunotherapy therapy treatment, if required, and be followed after their primary treatment is finished. Holding the clinic in the local setting reduces the travel and time away from home for cancer patients. It is hoped this type of care can be expanded in the remote areas of the country.